Gathering the sun : an A B C in Spanish and English - Ada, Alma Flor; Silva, Simon (New York : Lothrop, Lee & Shepard Books, 1997)
A book of poems about working in the fields and nature's bounty, one for each letter of the Spanish alphabet.
Spanish and English.
Keywords: Children's poetry, Hispanic American (Spanish); Spanish language -- Alphabet; Agricultural laborers -- Juvenile poetry; Hispanic American poetry (Spanish); Alphabet; Agricultural laborers -- Poetry; Spanish language materials -- Bilingual